Bancroftian Filariasis Still Endemic in Some Foci in Sohag Governorate, Upper Egypt - Refaat MA Khalifa; Amal M Ahmed; Mohamed AA Taha; Nasr Eldeen MM Ali; Haitham KA Abd El Samea (Journal of Parasite Research, 2019)
Bancroftian filariasis (BF) is a debilitating disease that has plagued Egypt since the time of the pharaohs. Egypt is the first large endemic country in the world to reach the five-year mark in its national campaign. Now that the mass treatments are completed, a follow-up epidemiological assessment will reveal whether this large-scale, pioneering campaign has been successful in finally eliminating the disease. Hence the aim of the present work was to detect the prevalence of bancoftian filariasis in Tema, El-Maragha, Akhmeem and Girga districts in Sohag Governorate, Upper Egypt. Finger prick thick blood films were randomly collected from 500 clinically suspected individuals representing different sexes and ages suffering from lower limb non-pitting edema and/or inguinal lymphadenitis from May 2015 to February 2017. Three patients (0.6%) were infected with microfilariae of Wuchereria bancrofti while one chronic case was detected with severe chronic elephantiasis that was amicrofilaraemic but was confirmed serologically. Results were discussed in regards of age, gender, occupation, locality and residence. It was concluded that bancroftian filariasis is still endemic in three districts (Tema, El- maragha and Girga). Although in sporadic few cases, the problem should be taken seriously as one microfilaramic patient could be a patent reservoir for spreading of the disease through infecting the prevailing Culex pipiense mosquito intermediate host.
Keywords: Bancroftian Filariasis